Measurement and modeling of RFID propagation channel with in an indoor environment - Duangsuwan, S.; Promwong, S.; Sukutamatanti, N. (My University, 2008)
The radio frequency identification (RFID) technology was automatic identify becomes was essential in the service an indoor environment such as contactless smart card and libraries [10] at high frequency in free space transfer function in wireless communication usually consider used Friss's formula for analysis. This paper the RFID propagation channel at 2.45 GHz with indoor environment. The measurement result are evaluation by using Friis's transmission formula to find the magnitude and phase channel transfer function, path loss, and power delay profile. This technique is very useful for analyzed the signal strength and radio propagation loss of RFID transmission signal © 2008 IEEE.
Keywords: Antenna transfer function; Friis's transmission formula; Propagation channel; RFID